HRMAS NMR Spectroscopy to Identify the Primary Metabolome of Bracigliano PGI Sweet Cherries and Correlate It with Nutraceutical and Quality Parameters - Domenico Liguori; Pierluigi Mazzei (Foods)
In 2023, the Italian Bracigliano sweet cherries were awarded the important European label PGI. However, reliable information on the compositional and nutraceutical quality of this product is still relatively undefined and fragmented. Therefore, we investigated fresh Bracigliano PGI cherries (Pallaccia, Spernocchia, and Principe varieties) via HRMAS NMR spectroscopy in the semi-solid state, even though it represents an innovative and powerful technique that is still drastically unexplored. We demonstrated the HRMAS NMR suitability for this fruit type as well as identified the primary metabolome of studied Bracigliano PGI types. Moreover, chemometric techniques (ANOVA, PCA, and PLS-DA) permitted the significant definition of a variety-specific compositional fingerprint. HRMAS data were associated with the assessment of chemical and nutraceutical quality parameters. Importantly, in all studied varieties, a relatively high content of total phenols and antioxidant agents was detected, with Pallaccia cherries resulting as the healthiest ones. The heatmap clusterization revealed interesting correlations between HRMAS-NMR data and important quality parameters. Our results confirm the role of HRMAS in food chemistry and invite the creation of a spectral database of Bracigliano sweet cherries, useful to conduct traceability studies, protect consumers from frauds, and bolster the producers in promoting and certifying the quality of their products.